The research progress on radionuclides in osteoporosis diagnosis and drug efficacy monitoring - Fu, Jie; Zhang, Chi (Frontiers in Pharmacology, 2025)
Osteoporosis is a common metabolic bone disease that seriously affects the quality of life and health of patients. Traditional diagnostic methods, such as dual energy X-ray absorptiometry (DXA), have limitations in early detection and dynamic monitoring, making it difficult to meet clinical needs. This paper focuses on the potential of radionuclide imaging techniques, such as Single Photon Emission Computed Tomography (SPECT) and Positron Emission Tomography (PET), in the early diagnosis of osteoporosis. The paper further elaborates on the importance of radionuclides in evaluating the therapeutic effect of osteoporosis drugs. By summarizing current research findings, this paper aims to emphasize the core role of radionuclides in the management of osteoporosis, and provide theoretical basis and practical guidance for optimizing the diagnosis and treatment strategies of bone metabolism diseases in the future.